A Misdiagnosed Case of Double Outlet Right Atrium Associated With Hypoplastic Right Ventricle. Issue 3 (May 2020) - Raso, Irene; Quarti, Andrea; Chessa, Massimo; Basile, Domenica Paola; Saracino, Antonio; D'Aiello, Angelo Fabio; Raineri, Claudia; Carminati, Mario; Giamberti, Alessandro
Double outlet right atrium (DORA) is a rare congenital heart disease in which the right atrium opens into both ventricles. The reduced leftward motion of the interventricular septum causes a malalignment between the atrial and the ventricular septum at the cardiac crux, which is the pathognomonic feature of this heart defect. We describe a case of significant exertional desaturation in an adult patient who was diagnosed with DORA, restrictive right ventricle, and anomalous tricuspid valve. Subsequently, the patient underwent one-and-a-half ventricular palliation.